FINITE ELEMENT MODELS OF POST-TENSIONED MASONRY COLUMNS - Made Budiwati, Ida Ayu (Jurnal Ilmiah Teknik Sipil; Vol. 12, No. 2 Juli 2008)
Applications of finite element method in modelling dynamic problems can be used to predict structural dynamic behaviour. In this paper the post-tensioned masonry column was modelled in 2D and 3D using two finite element analysis computer programs, LUSAS and ABAQUS. The frequency analyses were carried out to determine natural frequencies and the corresponding mode shapes of post-tensioned masonry columns. The effects of increasing post-tension force on the natural frequencies of the columns were determined A comparison was made between the 2D and 3D models and also between the two programs used by way of their natural frequency results. It has been shown that the natural frequencies of post-tensioned masonry column with zero post-tension force comprise the natural frequencies of its individual components (the masonry column with the concrete cap only and the post-tensioning bar only). With increasing post-tension force the natural frequency increased. Natural frequencies obtained using 2D models were in general higher than those of 3D models and ABAQUS results were almost smaller than LUSAS results. Nevertheless, it is appropriate to model dynamic behaviour of post-tensioned masonry in 2D and to use any of the two programs.
Keywords: LUSAS, ABAQUS, finite element software, natural frequency, post-tensioned masonry